Pengaruh Motivasi Karir Mengajar Terhadap Prestasi Akademik Mahasiswa Pendidikan Sosiologi Untirta - Janu Shyam Bachtiar; Wahid Abdul Kudus (Jurnal Pendidikan Indonesia, 2022)
The government made a breakthrough to open a PPPK recruitment path for temporary workers. This decision is certainly a hope for prospective teacher students and teachers themselves to have a career as an educator. This study aims to examine the effect of teaching career motivation on academic achievement. The research location was conducted at the University of Sultan Ageng Tirtayasa (Untirta) with research subjects of 2019 Sociology Education students. The research method used was survey research with a descriptive approach. The data collection technique was carried out with a questionnaire instrument compiled using google form. The respondents of this study were all students of Sociology Education Untirta batch 2019. Data analysis was carried out using descriptive statistical techniques. The results showed that based on the t-test obtained a significance value of 0.000 <0.05, so it can be concluded that the Teaching Career Motivation variable (X) has an effect on the Academic Achievement variable (Y). Then, decision making based on the t test, it is known that the t count is 9.159 > t table 1.998, so it can be concluded that the Teaching Career Motivation variable (X) has an effect on the Academic Achievement variable (Y).